Planning for Investment in Energy Innovation: Developing an Analytical Tool to Explore the Impact of Knowledge Flow - Miremadi, Iman; Saboohi, Yadollah (International Journal of Energy Economics and Policy, 2018)
Energy innovation is a key requirement to limit global warming and tackle climate change in the years to come. A better understanding of the knowledge flow mechanism is likely to improve allocation of resources for energy innovation. The major objective of this study is to provide an analytical tool to identify the role of investment on innovation in the process of new technologies development. To achieve this goal, a model of knowledge flow is developed and the effects of national and international knowledge spillovers are investigated. Results show that when knowledge spillovers are modelled in the Nordic countries, the required investment on domestic energy R&D decreases and the cumulative knowledge increases to 10.7 billion USD by 2030. This is a significant economic potential for technological innovation which can be considered for both energy researchers and energy planners. Finally, some important policy insights and some recommendations for further research are concluded. Keywords: Energy economics; R&D expenditure; Knowledge spillovers; Energy policy. JEL Classifications: Q43, O3